Marcos estratigraficos regionais na Formacao Palermo: caracterizacao dos picos radioativos - Perinotto, José Alexandre de Jesus [UNESP]; Bonotto, Daniel Marcos [UNESP] (My University, 1994)
During a basinal scale study on Palermo Formation (Upper Permian, Parana Basin) high elevated Gamma Ray picks were identified mainly in the lower third of that stratigraphic unit. Those Gamma Ray signatures have been used as good regional stratigraphic markers. From them it was possible one chronostratigraphic analysis of Palermo Formation as pointed out by previous papers (Perinotto). Potassium40 is the responsible for the high Gamma Ray picks in the Palermo Formation. -from English summary
Regional stratigraphic benchmarks in the Palermo Formation: characterization of radioactivity peaks
Keywords: chronostratigraphy; gamma ray anomaly; Permian; potassium-40; stratigraphy; Brazil, Parana Basin